Anthropology: The Explorating Of Human Diversity - Conrad Phillip Kottak (Mc Graw Hill, 2008)
This book has three main goals. First goal is to offer a thorough up to date, and holistic introduction to anthropology that systematically approaches the course from a four field perspective